2021
DOI: 10.3390/en14185609
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Ensuring Energy Security with the Use of Hard Coal—The Case of Poland

Abstract: In this article, the authors present methods based on hard coal that may ensure energy security for European Union countries. The research was carried out based on the example of Poland. The main reason for which coal is being gradually withdrawn from the energy mixes in EU countries is its negative impact on the natural environment and the health of citizens and economic factors related to domestic fuel production. The authors propose the creation of energy–chemical clusters as a solution to these problems. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…For this purpose, it was first necessary to determine measures and explanatory variables that would make it possible to verify the existence of such a relationship. Based on the authors' experience [27,29] and literature review [2,3,5,6,9,10,12,25,34,45], the set of indicators presented in Table 1 was adopted for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, it was first necessary to determine measures and explanatory variables that would make it possible to verify the existence of such a relationship. Based on the authors' experience [27,29] and literature review [2,3,5,6,9,10,12,25,34,45], the set of indicators presented in Table 1 was adopted for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture of gases produced in the coal combustion process constitutes the feed solution, which, after passing through the membrane, is separated into permeate and retentate. Retentate is a mixture of greenhouse gases (mainly carbon oxides, but also sulphur and nitrogen oxides), which can be additionally separated in order to be captured, stored or further processed and used [29]. Despite numerous advantages, membranes also have disadvantages, mainly chemical and mechanical resistance, as well as the need to regenerate membranes [30].…”
mentioning
confidence: 99%
“…According to the authors, it is necessary to redefine the priorities and promoted energy sources. As the authors have suggested in their previous publications [22,54], and as shown by recent events, basing the EU's energy security on raw materials imported from politically unstable regions of the world is very risky. This applies not only to oil and gas imported from Russia, but also Arab countries.…”
Section: Discussionmentioning
confidence: 99%
“…The authors believe that CCU is an even more advantageous solution. This is because it enables the generation of additional profit through the management of carbon dioxide and its use, for example, during the oil extraction or biomass production process [21,22]. For this purpose, the authors proposed a membrane technology that allows the separation and thus purification of the gas mixture formed during the combustion of fossil fuels, including coal, natural gas and crude oil.…”
mentioning
confidence: 99%
“…In 2007, EU leaders set a target of reducing the EU's annual energy consumption by 20% by 2020. In 2018, the Clean Energy for All Europeans package set a new target of reducing energy consumption by at least 32.5% by 2030 [2][3][4][5][6]. Ensuring energy efficiency is increasingly recognized not only as a means of ensuring a sustainable energy supply, reducing greenhouse gas emissions, increasing security of supply and reducing energy import expenses but also as promoting the EU's competitiveness.…”
Section: Introductionmentioning
confidence: 99%